Effect of piperazine (PIP) concentration and reaction time on the formation of thin film composite forward osmosis (FO) membrane - Mohammad Amirul, Mohd Yusof; Mazrul Nizam, Abu Seman (Penerbit Universiti Teknologi Malaysia, 2017)
Nowadays, wide applications of forward osmosis (FO) technology have been huge attention in solving the water shortage problems. Hence, the performance of thin film composite (TFC) forward osmosis membrane via interfacial polymerization (IP) was studied. 2% and 1% w/v of piperazine (PIP) and 0.15% w/v of trimesoyl chloride (TMC) were reacted with 3 different reaction time (60s, 30s, and 10s). The fabricated membranes were then characterized by FTIR, contact angle measurement and FESEM. Pure water flux, humic acid rejection (represent NOM) and salt leakage were evaluated to obtain the best polyamide FO membrane. The results demonstrated that polyamide FO membranes fabricated with 2% w/v possess a higher hydrophilic properties compared to 1% w/v. In addition, regardless of monomer concentrations, at longest reaction time (60s), there is no significant change in water flux. Membrane fabricated at 60s of reaction time exhibited water flux of 1.90 LMH and 1.92 LMH for 2% w/v and 1% w/v of PIP concentrations, respectively. The same trend also observed for humic acid rejection (93.9%-94.6%). The salt leakage test revealed that the minimum salt reverse diffusion (0.01-0.02 GMH) could be achieved for membrane fabricated at longest reaction time of 60s for both PIP concentrations. As conclusion, manipulating monomer concentrations and reaction time is the main key to obtain an optimal polyamide layer with high membrane performance covering higher water flux, higher removal of humic acid and lower reverse salt diffusion.